2010
DOI: 10.2478/v10045-010-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Metarhizium Anisopliae (Ascomycota: Hypocreales) with Several Insectisides

Abstract: Abstract:The entomopathogenic fungus conidia viability and sporulation may be affected by different environmental factors or by bio-pesticides and chemical products used to protect cultivated plants. In this research, we investigated the compatibility of Metarhizium anisopliae DEMI 001 isolates with three insecticides: fipronil, pyriproxyfen and hexaflumuron. The effect of fipronil, pyriproxyfen and hexaflumuron on sporulation, vegetative growth and conidial germination of the fungus was studied based on measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…A relatively small effect of insecticides on the growth and germination of entomopathogenic fungi compared to fungicides and herbicides has been observed (Mi臋tkiewski et al 1997;Tkaczuk et al 2013). Other studies have shown that insecticides: fipronil, pyriproxyfen and hexaflumurion, significantly reduced the conidial germination of M. anisopliae under laboratory conditions (Rashid et al 2010).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A relatively small effect of insecticides on the growth and germination of entomopathogenic fungi compared to fungicides and herbicides has been observed (Mi臋tkiewski et al 1997;Tkaczuk et al 2013). Other studies have shown that insecticides: fipronil, pyriproxyfen and hexaflumurion, significantly reduced the conidial germination of M. anisopliae under laboratory conditions (Rashid et al 2010).…”
Section: Discussionmentioning
confidence: 86%
“…It is important to know the side effects of pesticides on beneficial organisms for IPM. It is known that pesticides can have different effects on growth, sporulation and pathogenicity of entomopathogenic fungi (Majchrowicz and Poprawski 1993;Tkaczuk 2001;Rashid et al 2010;Hernandez et al 2012;Tkaczuk et.al. 2012Tkaczuk et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Another research revealed, however, no or negative impact of insecticides on entomopathogenic fungi. Rashid et al [2010], for example, found that insecticides: fipronil, pyriproxyfen and hexaflumuron significantly reduced the conidial germination of Metharizium anisopliae under laboratory conditions. Tested in this study insecticide lambda-cyhalothrin slightly reduced the size of fungal colonies, which make it suitable for compatible use with entomopathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Celar dan Kos (2012) juga berpendapat bahwa B. bassiana sangat peka terhadap beberapa senyawa bahan aktif pada herbisida kimia yang diuji, karena dosis rekomendasi terendah di lapang sudah mampu menekan lebih dari 75% pertumbuhan kedua entomopatogen tersebut. Rashid et al (2010) melaporkan bahwa perlakuan insektisida kimia hexaflumuron pada konsentrasi 120 ppm telah menghentikan pertumbuhan vegetatif cendawan M. anisopliae (100%), Tabel 1. Diameter koloni Beauveria bassiana pada media agar kentang dekstrosa dengan berbagai konsentrasi pupuk organik cair.…”
Section: Hasil Dan Pembahasan Kompatibilitas B Bassiana Dengan Pocunclassified
“…Note : Numbers followed by same letter in the same column were not significantly different at 5% level of DMRT Bb = Beauveria bassiana POC = pupuk organik cair/liquid organic fertilizer tertinggi dibanding pyriproxyfen (24,59%) dan fipronil (24,31%). Oleh karena itu, Rashid et al (2010) tidak merekomendasikan penggunaan insektisida berbahan aktif hexaflumuron bersamaan dengan cendawan entomopatogen. Minyak seraiwangi dan minyak cengkeh juga dilaporkan menurunkan efektivitas B. bassiana jika dicampurkan dengan cendawan tersebut dan diaplikasikan terhadap hama pengisap pucuk jambu mete Helopeltis antonii Sign (Hemiptera: Miridae).…”
Section: Hasil Dan Pembahasan Kompatibilitas B Bassiana Dengan Pocunclassified